2015
DOI: 10.1016/j.irfa.2015.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Do fund managers herd in frontier markets — and why?

Abstract: Frontier markets constitute a category of markets for which very little is known regarding the behaviour of their institutional investors. This study attempts to shed light on this issue by investigating whether fund managers herd in frontier markets and whether their herding is intentional or not using data on quarterly portfolio holdings of funds from two such markets (Bulgaria and Montenegro). Results show that fund managers herd significantly in both markets; controlling for the interaction of their herdin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Herding is found to be more pronounced in emerging markets than in developed markets (Borensztein & Gelos, 2003). Other studies on developing equity markets include, Economou, Gavriilidis, Kallinterakis, and Yordanov (2015) which examine herding in frontier markets; Chang et al (2000) and Demirer, Kutan, and Chen (2010) in Taiwan financial market; Tan et al (2008) and Chiang and Zheng (2010)) investigate herding in Chinese equity markets; and Rahman et al (2015) and many other assess herding in the GCC equity markets 10 . Our study is related to these studies but we are distinguished by accounting for fundamental and style co‐movements in return premia before drawing our inferences on herding in Saudi equities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Herding is found to be more pronounced in emerging markets than in developed markets (Borensztein & Gelos, 2003). Other studies on developing equity markets include, Economou, Gavriilidis, Kallinterakis, and Yordanov (2015) which examine herding in frontier markets; Chang et al (2000) and Demirer, Kutan, and Chen (2010) in Taiwan financial market; Tan et al (2008) and Chiang and Zheng (2010)) investigate herding in Chinese equity markets; and Rahman et al (2015) and many other assess herding in the GCC equity markets 10 . Our study is related to these studies but we are distinguished by accounting for fundamental and style co‐movements in return premia before drawing our inferences on herding in Saudi equities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fund managers, for example, tend to exhibit significantly higher levels of herding in Portugal (Holmes et al, 2013), South Korea (Choe et al, 1999) and Taiwan (Chang, 2010;Lu et al, 2012), compared to Spain (Gavriilidis et al, 2013), the UK (Wylie, 2005), Germany (Walter and Weber, 2006;Kremer and Nautz, 2013) and the US (Lakonishok et al, 1992;Grinblatt et al, 1995;Wermers, 1999;Sias, 2004;Choi and Sias, 2009). Evidence from frontier markets (Economou et al, 2015b) has shown that they also accommodate substantial institutional herding, whose levels are significantly higher compared to those documented in emerging markets. The picture remains similar when assessing herding at the aggregate market level.…”
Section: Introductionmentioning
confidence: 96%
“…Given the relatively limited research on frontier markets' herding and its determinants (Balcilar et al, 2013;Economou et al, 2015b), our study contributes in that direction by investigating herding in African frontier stock exchanges, addressing several research questions. First, we examine whether herding is significant in frontier markets in Africa and whether it presents us with size-effect, in view of the low trading activity and high market concentration typifying frontier markets in general.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we test for asymmetric herd behavior effects in terms of extreme market movements, contraction and expansion phases; and whether there are any spill-over herding effects from one market 2 In the drybulk market, the efficient market hypothesis (EMH) and asset pricing models focus mainly on the term structure of freight rates, vessel price formation, risk premium and trading strategies (Kavussanos and Alizadeh, 2002;Adland and Koekebakker, 2004;Kavussanos et al, 2004;Adland and Strandenes, 2006;Alizadeh and Nomikos, 2006;Alizadeh and Nomikos, 2007). However, herding behavior may not always be regarded as an anomaly which contradicts the efficient market hypothesis; rather, if it is assumed that investors trade in the direction of informed investors, then asset prices may converge faster to their fundamental values (Gavriilidis et al, 2013;Economou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%